2022
DOI: 10.1002/smll.202202623
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into to the KX (X = Cl, Br, I) Adsorption‐Assisted Stabilization of CsPbI2Br Surface

Abstract: diffusion length, and high light absorption coefficient. [7][8][9] These research efforts have witnessed the steady promotion of their power conversion efficiencies (PCEs) from 3.8% to 25.5%. [10] Nonetheless, the instability of the organic components against light, humidity, and heat remains the most pernicious problem jeopardizing their commercial applications. [11][12][13] It is therefore recommended to replace the organic components with inorganic cations, one example being α-CsPbI 2 Br, [14][15][16][17][1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…The projector-augmented wave (PAW) approach was used to describe electron-ion interactions [51]. The generalized gradient approximation of the Perdew-Burke-Ernzerhof (PBE) functional and the Heyd-Scuseria-Ernzerhof (HSE06) hybridization function were employed for geometry optimizations and self-consistent static calculations, respectively [52][53][54][55][56]. Spin-orbit coupling (SOC) was considered.…”
Section: Dft Calculationsmentioning
confidence: 99%
“…The projector-augmented wave (PAW) approach was used to describe electron-ion interactions [51]. The generalized gradient approximation of the Perdew-Burke-Ernzerhof (PBE) functional and the Heyd-Scuseria-Ernzerhof (HSE06) hybridization function were employed for geometry optimizations and self-consistent static calculations, respectively [52][53][54][55][56]. Spin-orbit coupling (SOC) was considered.…”
Section: Dft Calculationsmentioning
confidence: 99%
“…Polymer dielectrics are core frameworks that constitute the insulation systems in power systems and advanced electronic devices. [1][2][3][4] Due to the development of highly integrated and Therefore, in this study, different concentrations of zinc oxide (ZnO)−polydimethylsiloxane (PDMS) coatings were prepared from ZnO nanoparticles with PDMS used as the binder. The coatings were applied to the surfaces of several widely used polymer dielectric films, and it was found that the breakdown strengths of the coatings were significantly improved.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer dielectrics are core frameworks that constitute the insulation systems in power systems and advanced electronic devices. [ 1–4 ] Due to the development of highly integrated and high‐powered electrical and electronic devices, polymer dielectrics need to withstand increasingly larger working electric fields. [ 2–4 ] In addition, polymer dielectrics are the basis for fabrication of energy storage film capacitors, [ 5–7 ] and the maximum energy storage density of a polymer dielectric is proportional to the square of the breakdown field strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19,25] However, there are few studies on this aspect, and there is a lack of in-depth research on the physical mechanisms. In addition, although research on deeplevel defect states is of great significance and a suitable passivation agent is an effective means of eliminating deep-level defect states, [26][27][28] there is little research on suitable passivators and even less research on passivation of polymer dielectric deeplevel defect states. There is no systematic in-depth exploration of passivation mechanisms from the perspective of the physical mechanisms.…”
mentioning
confidence: 99%